OIL SPILL SIMULATION IN THE BALI STRAIT USING THE GNOME AND FVCOM MODELS ON EASTERLY SEASON - Putu Hadi Wiguna, Pande; Hendrawan, I Gede; Osawa, Takahiro (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 17 No 2 (2023), 2023)
Among several forms of marine pollution, oil damages coastal ecosystems. Repeated reports of oil contamination in the marine environment can partly load with major shipping lines. The Ketapang-Gilimanuk crossing over the Bali Strait is Indonesia's second busiest ferry port after Merak-Bakauheni. The most congested shipping routes can carry a significant risk of environmental damage from an oil spill. Oil spill trajectory modelling is carried out to reduce the impact of this possible disaster. Therefore, the use of modelling to ascertain the route of the oil spill was considered. The oil leak path is simulated using the GNOME model. Two oil spill scenarios were used as input models. The chosen location is around the Ketapang Gilimanuk crossing, as well as the time of the easterly season. An ocean HF radar stationed in the Bali Strait verifies the accuracy of the current marine data generated by FVCOM. To see the pattern of the oil spill trajectory based on a ten days simulation, we combined the latest data from FVCOM with GNOME. To determine the ability of the model to predict the flow and trajectory of oil spills in the Bali Strait, this study try to analyze and interpret the oil spill trajectory from model and then validate the model results with satellite imagery. Keywords: Bali strait; oil spill; trajectory; GNOME; FVCOM; HF Radar